2021
DOI: 10.5114/aoms/130648
|View full text |Cite
|
Sign up to set email alerts
|

Serum S100A8 as an early diagnostic biomarker in patients with community-acquired pneumonia

Abstract: IntroductionLimited studies have suggested that calprotectin may take part in the pathophysiology of community-acquired pneumonia (CAP). Nevertheless, there is no clinical study analysing the role of S100A8 in CAP patients. The objective of this study was to analyse the association of serum S100A8 with the severity of CAP and determine the cut-off values of S100A8 for predictive power based on a cross-sectional study.Material and methodsA total of 200 CAP patients and 100 normal subjects were recruited. Demogr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
4
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
5

Relationship

2
3

Authors

Journals

citations
Cited by 5 publications
(4 citation statements)
references
References 35 publications
0
4
0
Order By: Relevance
“…All selected 239 CAP patients in this research must meet certain diagnostic standard: In accord with the clinical manifestations of pneumonia and consistent with chest CT scans, mainly including (1) chest radiograph suggesting either a new patchy infiltrate, leaf or segment consolidation, ground glass opacity or interstitial change; (2) at least one of the following signs: the presence of cough, sputum production and dyspnoea; core body temperature higher than 38.0 °C; auscultatory findings of abnormal breath sounds and rales; or the counts of white blood cell more than 10 × 10 9 L or less than 4 × 10 9 L; (3) occurred in the community, rather than in a hospital [ 22 ]. The inclusion criteria were as follows: pneumonia was occurred in the community or within a definite incubation period after hospitalization; these candidates were not admitted to the hospital for the last three months; not pregnant; no other pulmonary diseases, such as pulmonary malignant tumor, pulmonary tuberculosis or immunodeficiency [ 23 , 24 ]; no antibiotic treatment or intervention before hospitalization. Peripheral blood samples were collected and anticoagulated with EDTA within 24 h after hospitalization.…”
Section: Methodsmentioning
confidence: 99%
“…All selected 239 CAP patients in this research must meet certain diagnostic standard: In accord with the clinical manifestations of pneumonia and consistent with chest CT scans, mainly including (1) chest radiograph suggesting either a new patchy infiltrate, leaf or segment consolidation, ground glass opacity or interstitial change; (2) at least one of the following signs: the presence of cough, sputum production and dyspnoea; core body temperature higher than 38.0 °C; auscultatory findings of abnormal breath sounds and rales; or the counts of white blood cell more than 10 × 10 9 L or less than 4 × 10 9 L; (3) occurred in the community, rather than in a hospital [ 22 ]. The inclusion criteria were as follows: pneumonia was occurred in the community or within a definite incubation period after hospitalization; these candidates were not admitted to the hospital for the last three months; not pregnant; no other pulmonary diseases, such as pulmonary malignant tumor, pulmonary tuberculosis or immunodeficiency [ 23 , 24 ]; no antibiotic treatment or intervention before hospitalization. Peripheral blood samples were collected and anticoagulated with EDTA within 24 h after hospitalization.…”
Section: Methodsmentioning
confidence: 99%
“…Fang et al investigated the correlations between the serum S100A8 heterodimer and the severity of community-acquired pneumonia (CAP) and inflammatory cytokines in adults [ 79 ]. Another objective was to establish S100A8 cutoff values for predictive power in CAP patients.…”
Section: Cp and Respiratory Infectionsmentioning
confidence: 99%
“…However, the role of 4-HNE was unclear in patients with CAP. Some studies from our team have demonstrated that inflammation and oxidative stress exert important roles in the pathophysiology of CAP (29)(30)(31)(32). Hence, it is reasonable to infer that 4-HNE may be involved in the process of CAP.…”
Section: The Predictive Powers For Severity and Deathmentioning
confidence: 93%